Antimetabolite activity and metabolites of Aspergillus flavipes ATCC 11013 - Clark, Alice Mae 1951-
As part of a screening program of higher plants and fungal culture filtrates for antimetabolite activity, it was found that culture filtrates of Aspergillus flavipes ATCC 11013 exhibited significant antimetabolite activity. The production of antimetabolite activity reaches an optimum between day 8 and day 10 of growth. Thin layer chromatographic, bioautographic, and column chromatographic studies indicates that the antimetabolite activity is due to a complex mixture of components which could not be isolated in pure form. During the course of the attempted isolation of the active constituents, two novel fungal metabolites were isolated. Compound IV, C16 H17 NO2, was isolated by chromatography of the chloroform extract of the culture filtrate. The spectroscopic evidence suggested the presence of a benzyl group, a benzamide, and a primary alcohol. Compound IV was identified as (S)-N-benzoylphenylalaninol by direct comparison with an authentic sample. Compound III, C32 H30 N2 O4, was obtained by chromatography of the chloroform of the fungal mycelium. The UV and 1H NMR data for III were similar to that of IV. The IR spectrum shows prominent bands for an ester and a secondary amide. Mild basic hydrolysis yielded two products which were identified as (S)-N-benzoylphenylalaninol and (S)-N-benzoyl-phenylalanine by comparison with authentic samples. The 13C NMR data along with the other chemical and spectroscopic evidence allows formulation of compound III as (S)-N-benzoylphenylalanine-(S)-2-benzamido-3-phenylpropyl ester.